Pengaruh Pengalaman Kerja, Kompetensi Dan Moralitas Individu Terhadap Pencegahan Fraud Dalam Pengelolaan Dana Desa (Studi Empiris Di Desa Kecamatan Kartasura, Sukoharjo) - Yudana Putra Difajar; Nursiam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to empirically prove the influence of work experience, competence, and individual morality on fraud prevention in village fund management. The approach used is quantitative with associative methods. The population in this study were village government officials in Kartasura District, with sampling using purposive random sampling techniques based on criteria such as position, minimum education of high school/vocational school, and minimum work experience of one year. Data collection was carried out through questionnaires that had been tested for validity and reliability. Classical assumption tests such as normality, multicollinearity, and heteroscedasticity were carried out to ensure the feasibility of the multiple regression model. The results of the analysis showed that work experience, competence, and individual morality had a significant effect on fraud prevention in village fund management. This finding emphasizes the importance of improving the quality of human resources in order to strengthen accountable and transparent village financial governance.